Dampak Literasi Media Berbasis Digital Terhadap Perilaku Anti Penyebaran Hoaks - Haryadi Mujianto; Zikri Fachrul Nurhadi (UIN Antasari Banjarmasin, 2022)
Digitalization brings benefits to the development of communication media around the world. Now communication can be done interactively and in real-time through digital media. Social media is a popular digital communication media used by teenagers to interact socially. The phenomenon that occurs is a change in behavior and activities of social media users, especially teenagers. The ease of accessing and exchanging information gives rise to the phenomenon of the spread of hoaxes. Kominfo revealed that there were 565,449 hoax content circulating through social media throughout 2021. This study aims to determine the impact of digital-based media literacy on the behavior of anti-spreading hoaxes among teenagers. This research uses quantitative and verification methods. Data was collected by distributing questionnaires to 100 respondents from SMA Negeri 2 Lembang students. Samples were taken based on purposive sampling category. Data analysis used simple linear regression with the help of SPSS software version 20.0. The results showed that there was a significant negative impact of digital-based media literacy on the behavior of anti-spreading hoaxes among adolescents with a coefficient of determination of 73.4%, while the remaining 53.8% was influenced by other variables not examined.